Ruang Lingkup Asset And Liabillity Management (ALMA) - Fitri Andina, Dwitya; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (MUI Kota Pekanbaru, 2024)
An asset management system cannot do without liability management. These two systems are like two sides of a coin, connected to each other. The reason is that most sources of bank assets are obtained from deposits, even though the bank has its own capital, its liabilities are more profitable than its own capital. Therefore, the development of assets is influenced by the increase in liabilities. Judging from the composition of the bank's balance sheet, the left side is the assets owned, and the right side is the liabilities to stakeholders. To balance these two aspects, banks need an effective and efficient management system. Therefore, banks implement ALMA (Asset Liability Management). This writing uses a type/approach method in the form of library research. ALMA is a series of actions and procedures designed to control financial positions. Asset and Liability Management is also to manage risks that may arise in daily business activities which are then specifically designed so that they can optimize income while limiting asset and liability risks by complying with monetary policy and bank supervision. The implementation of asset and liability management in banking institutions, both Islamic and conventional banks, must go through the stages of budget assessment, making income plans, assessing past investment performance, monitoring the distribution of bank assets and liabilities and implementing asset and liability strategies. An asset management system cannot do without liability management. These two systems are like two sides of a coin, connected to each other. The reason is that most sources of bank assets are obtained from deposits, even though the bank has its own capital, its liabilities are more profitable than its own capital. Therefore, the development of assets is influenced by the increase in liabilities. Judging from the composition of the bank's balance sheet, the left side is the assets owned, and the right side is the liabilities to stakeholders. To balance these two aspects, banks need an effective and efficient management system. Therefore, banks implement ALMA (Asset Liability Management). This writing uses a type/approach method in the form of library research. ALMA is a series of actions and procedures designed to control financial positions. Asset and Liability Management is also to manage risks that may arise in daily business activities which are then specifically designed so that they can optimize income while limiting asset and liability risks by complying with monetary policy and bank supervision. The implementation of asset and liability management in banking institutions, both Islamic and conventional banks, must go through the stages of budget assessment, making income plans, assessing past investment performance, monitoring the distribution of bank assets and liabilities and implementing asset and liability strategies.